2015
DOI: 10.1017/s0022215114002527
|View full text |Cite
|
Sign up to set email alerts
|

Primary otological manifestations of granulomatosis with polyangiitis: a case series

Abstract: When acute supposed ear infections fail to respond to treatment (antibiotics or surgery), rarer causes of the symptoms should be considered. By reporting this case series, we aim to improve the early diagnosis of granulomatosis with polyangiitis to enable timely treatment and prevent systemic involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“… 1 4 American College of Rheumatology, American Society of Nephrology and the European League Against Rheumatism suggested that the name should be changed to GPA. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 4 American College of Rheumatology, American Society of Nephrology and the European League Against Rheumatism suggested that the name should be changed to GPA. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…However, c-ANCA can also be associated with other diseases, especially with rheumatoid arthritis. 1 , 2 , 7 , 8 Therefore, some cases of GPA are negative for c-ANCA. A positive identification of c-ANCA is suggestive of GPA, but cannot replace a biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In der Konsequenz ist insbesondere bei der bilateralen, rezidivierenden oder protrahierten Otitis media an eine autoimmunologische Erkrankung zu denken und nach c-ANCA zu suchen. Chirurgische Maßnahmen sind bei der Granulomatose mit Polyangiitis aufgrund des Risikos von protrahierten Heilungsverläufen zurückhaltend zu stellen [113].…”
Section: Granulomatose Mit Polyangiitisunclassified
“…Consequently, especially in bilateral, recurrent or protracted otitis media, an autoimmunological disease should be considered and c-ANCA should be sought. Surgical treatment should be carefully indicated in granulomatosis with polyangiitis due to the risk of protracted healing [113].…”
Section: Letterer-siwe Syndromementioning
confidence: 99%